Groundwater Quality of Southeastern Brazzaville, Congo - Matini Laurent; Moutou Joseph Marie (E-Journal of Chemistry)
The groundwater in southeastern Brazzaville (Congo) was analyzed for their fluoride contents and others related parameters in rainy season. The fluoride contents in water samples (wells and spring) can be gather in three classes in the study area: low, optimal, high. Fluoride concentration in water samples presents a low significant correlation with Ca2+. This suggests that fluoride in the groundwater come from fluoride-bearing minerals such as CaF2 (fluorite). Maps were drawn to show the geographical distribution of EC, Ca2+, Mg2+and F-. Factor analysis and cluster analysis were applied to the dataset. Factor analysis resulted in four factors explained 76.90% of the total groundwater quality variance. Factor 1 (hardness of the groundwater) includes total hardness, the concentration of K+, Ca2+ and pH. Factor 2 (low mineralization of the groundwater) includes concentrations of TDS, Cl--, SO42+ and EC. Factor 3 (anthropogenic activities with the impact of agricultural fertilizers, farming activities, domestic wastewater, septic tanks) includes concentrations of Na+ and NO3-. Factor 4 (weathering of calcium minerals) includes concentrations of F-. For cluster analysis, Ward’s method and the Euclidean distance were used. The findings of the cluster analysis are presented in the form of dendrogram of the well water sites (cases). The discriminating parameters between clusters have been highlighted from the Student test. In majority, they are in accordance with those highlighted by factor analysis.